Resilience and Syndemic Risk Factors among African American Female Sex Workers - Buttram, Mance E. (2013)
Research on street-based female sex workers documents a multitude of problems faced by these women, such as, substance use, HIV risk, mental health problems, victimization, and homelessness. The presence of problems such as these is understood as a syndemic, or co-occurrence of two or more risk factors that act synergistically to create an excess burden of disease. However, the syndemic framework has not previously incorporated the examination of resilience to understand what protective factors enable female sex workers to cope with syndemic risk. Using 562 baseline interviews from street-based African American female sex workers enrolled in a randomized intervention trial, this study is the first to investigate expressions of resilience among this vulnerable population. Specifically, these analyses examine high levels of resilience, as measured by personal mastery, in order to understand the contributions of syndemic risk factors and protective factors on the expression of resilience. In bivariate logistic regression models, women with high resilience reported significantly higher odds of high school education, greater access to transportation, and more social support, in addition to lower odds of foster care history, homelessness, substance dependence, severe mental distress, victimization, and HIV risk. In the multivariate model, higher odds of high school education and increased social support, in addition to lower odds of mental distress and HIV risk remained associated with high resilience. The findings suggest specific targets for intervention to assist female sex workers in coping syndemic risk factors and achieving better health outcomes. These include the prioritizing education and training opportunities and the enhancement of social support.